NC-1059, a channel forming peptide, induces a reversible change in barrier function of epithelial monolayers - Somasekharan, Suma (Kansas State University, 2008)
NC-1059 is a synthetic channel-forming peptide that provides for ion transport across, and transiently reduces barrier integrity of, cultured epithelial monolayers derived from canine kidney (MDCK cells; Broughman, J. R. et al; Am J Physiol Cell Physiol 286: C1312-23). In this first study experiments were conducted to determine whether epithelial cells derived from other sources were similarly affected. Human (T84, Calu-3) and non-human (IPEC-J2, PVD9902) epithelial cells derived from intestinal (T84, IPEC-J2), airway (Calu-3), and genitourinary (PVD9902) tissues were grown on permeable supports. Ion transport and barrier function were assessed electrically in a modified Ussing chamber. Basal short circuit current (I[subscript sc]) was typically less than 3 [Mu]A cm[superscript-2]. Apical NC-1059 exposure caused, in all cell types, an increase in I[subscript sc] to >15 [Mu]A cm[superscript-2], indicative of net anion secretion or cation absorption that was followed by an increase in transepithelial conductance (g[subscript te] in mS cm[superscript-2]; T-84, 1.6 to 62; PVD9902, 0.2 to 51; IPEC-J2, 0.3 to 26; Calu-3, 2.2 to 13). NC-1059 induces a concentration dependent change in the I[subscript sc] and g[subscript te] across these epithelia. The results in all cases were consistent with both a transcellular and a paracellular effect of the peptide. NC-1059 enhanced permeation of dextrans ranging from 10 kDa to 70 kDa across all epithelia tested. These results document an effect of NC-1059 on the paracellular route of epithelial barriers. Immunolabeling, confocal microscopy and immunoblotting methods were used in a second study to assess the molecular changes associated with increased paracellular permeability. NC-1059 induced a substantial reorganization of actin within 60 minutes of exposure. Confocal microscopy revealed that the changes in actin organization were accompanied by a pronounced change in the abundance and distribution of tight junction proteins occludin and ZO-1. Immunoblotting results suggest a time and concentration dependent effect on cellular abundance of these tight junction proteins. The effects on g[subscript te] and junctional proteins are transient with > 85% of recovery in 24 hours post exposure and full recovery within 48 hours. The reversible modulation of the epithelial tight junctions has therapeutic potential to increase the efficiency of drug delivery across barrier membranes.
Keywords: Epithelia; Paracellular; Tight Junctions; Conductance; Biology, Animal Physiology (0433); Biology, Cell (0379); Biophysics, General (0786)